2023
DOI: 10.3233/jad-221118
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Blood-Based Plasma Biomarkers as Potential Markers of Amyloid Burden in Preclinical Alzheimer’s Disease

Abstract: Background: Participant eligibility for the A4 Study was determined by amyloid PET imaging. Given the disadvantages of amyloid PET imaging in accessibility and cost, blood-based biomarkers may serve as a sufficient biomarker and more cost-effective screening tool for patient enrollment into preclinical AD trials. Objective: To determine if a blood-based screening test can adequately identify amyloid burden in participants screened into a preclinical AD trial. Methods: In this cross-sectional study, 224 partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…The impact of pre-analytical variables on Aβ40 and Aβ42 levels has been investigated in other studies. Unlike Winston et al, 24 Verberk et al 21 observed that storage of blood samples up to 24 hours at 4 • C before centrifugation does not have an impact on Aβ levels. Further studies should address the potential causes of these observed variations and compare the sensitivity of different platforms, for example, platforms that include an immunocapture step versus platforms such as ABtest-MS that does not, to this pre-analytical variable.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The impact of pre-analytical variables on Aβ40 and Aβ42 levels has been investigated in other studies. Unlike Winston et al, 24 Verberk et al 21 observed that storage of blood samples up to 24 hours at 4 • C before centrifugation does not have an impact on Aβ levels. Further studies should address the potential causes of these observed variations and compare the sensitivity of different platforms, for example, platforms that include an immunocapture step versus platforms such as ABtest-MS that does not, to this pre-analytical variable.…”
Section: Discussionmentioning
confidence: 93%
“…Regarding this last point, a recent study has revealed large differences in the predictive value of plasma Aβ42/Aβ40 when two different plasma collection protocols were applied in A4 samples 24 . Although a direct comparison is not possible, because the same samples have not been analyzed, when plasma samples were processed within 24 hours from blood extraction, the C2N's IP‐LC‐MS/MS technology identified amyloid‐PET status with an AUC of 0.64, notably worse than the 0.78 reported by ABtest‐MS in the present study in plasma samples processed with the same protocol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, these algorithms need to be validated in independent cohorts. As seen in two recent studies, the performance of plasma Aβ42/40 ratio in identifying brain amyloid status was improved when combined in an algorithm with apoE proteotype and age in one study, 70 but was not improved in the other one 71 …”
Section: Perspectivesmentioning
confidence: 90%
“…Furthermore, the Aβ42/Aβ40 ratio has been shown to have an inherently small dynamic range and hence low clinical robustness, 59 meaning that small technical differences when using the tests may result in patients being misclassified 59 . In addition, a 2023 publication found that including age, sex, and/or apolipoprotein E4 carrier status into a risk model did not improve the diagnostic performance compared to the plasma Aβ42/Aβ40 ratio alone, 60 a finding that should be considered when assessing the performance of tests that rely on the Aβ42/Aβ40 ratio in combination with age, sex, and/or apolipoprotein E4 carrier status.…”
Section: Potential Clinical Value Of Plasma Biomarker Testing In the ...mentioning
confidence: 99%